1978
DOI: 10.1111/j.1476-5381.1978.tb09751.x
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin Toxicity Compared With Myocardial Digoxin and Potassium Concentration

Abstract: 1 Twenty-nine dogs were given digoxin (0.25 mg) by mouth twice daily for eight days. Some of them (group 1) also received diuretics and others (group 2) a mineralocorticoid. The dogs were then given an intravenous bolus injection of digoxin and plasma and cardiac muscle were analysed for digoxin and potassium. 2 In the digitalized dogs, myocardial potassium concentration decreased following the intravenous injection of either 0.05 or 0.15 mg/kg digoxin; in contrast, in those dogs given diuretics or mineralocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…With digoxin, digitoxin and the aglycone k-strophanthidin in hypokalemia the expected decrease of the lethal doses (that means increase in toxicity) was observed. A similar change in toxicity by variation of the extracellular potassium concentration has already been reported in the intact animal (Marcus et al, 1969 andHall et al, 1977;Steiness, 1978) On the contrary, reports on the influence of extracellular potassiumvariations on the ouabain-induced toxicity are rather divergent and support in part the (unexpected) missing effect of the altered serum-potassium concentration in the present study. Whereas some findings in the dog as well as in the rabbit indicate the well-known potassium-digitalis antagonism for ouabain (Baker, 1947;Williams et al, 1966; Lown and Wittenberg, 1968), contradictory results have been reported in the guinea pig by Greeff and Knippers (1964) and Schaumann and Chatoor (1966).…”
Section: Discussionsupporting
confidence: 68%
“…With digoxin, digitoxin and the aglycone k-strophanthidin in hypokalemia the expected decrease of the lethal doses (that means increase in toxicity) was observed. A similar change in toxicity by variation of the extracellular potassium concentration has already been reported in the intact animal (Marcus et al, 1969 andHall et al, 1977;Steiness, 1978) On the contrary, reports on the influence of extracellular potassiumvariations on the ouabain-induced toxicity are rather divergent and support in part the (unexpected) missing effect of the altered serum-potassium concentration in the present study. Whereas some findings in the dog as well as in the rabbit indicate the well-known potassium-digitalis antagonism for ouabain (Baker, 1947;Williams et al, 1966; Lown and Wittenberg, 1968), contradictory results have been reported in the guinea pig by Greeff and Knippers (1964) and Schaumann and Chatoor (1966).…”
Section: Discussionsupporting
confidence: 68%
“…The same relationship between extracellular potassium and digitalis content in the myocardial tissue has been found by Cohn, Kleiger & Harrison (1967) and Steiness (1978). It seems that a pharmacodynamic effect of digitalis is influenced by potassium so that the lower potassium concentration increases the positive inotropic response considerably (Prindle et al, 1969).…”
Section: Discussionsupporting
confidence: 57%
“…The characteristics of the binding of the cardiac glycosides to this enzyme have been investigated both in fragments from cell membrane and in homogenates obtained from different tissues (Akera, Larsen & Brody, 1969). The binding of digitalis to the isolated (Na+ + K+) ATPase preparations and also the total amount of digitalis bound to intact myocardium are markedly influenced by the extracellular potassium concentration (Prindle, Skelton, Epstein & Marcus, 1969;Akera, Temma, Wiest & Brody, 1978;Steiness, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Their analyses also indicated that different thiazides could result in variation in the reduction of the serum potassium concentration. In addition, tubular secretion of digoxin is reduced when serum potassium concentrations are below 3 mmol l –1 [41]; i.e. hypokalaemia not only increases the serum digoxin concentration but also potentiates its toxicity [42].…”
Section: Discussionmentioning
confidence: 99%